2011
DOI: 10.1111/j.1365-2044.2011.06835.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant asymmetry of bispectral index during recovery from anaesthesia for ear-nose-throat surgery in adults and children

Abstract: SummaryThis study investigates the incidence of clinically relevant asymmetry in bispectral index readings from different sides of the skull (using two monitors) during ear-nose-throat surgery in 42 adults and 46 children. A unilateral increase or decrease > 10% from baseline was defined as an 'asymmetry'. Asymmetry followed by movement after stimulation was defined as a 'clinically relevant asymmetry'. Asymmetry occurred in 39 out of 42 adults (93%) and in 20 out of 46 children (44%) during surgery and in 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…[7,9, 10] Also, intraoperative asymmetry of the two sides was introduced in several studies. [5,11] Fudickar et al reported that BIS asymmetry occurred in 12% of adults during ear-nose surgery [5] and found that asymmetry was not related to the side position during surgery. This percentage was higher than that in our study (8.9%) and might be associated with unanticipated stimulation or movement during ear-nose surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7,9, 10] Also, intraoperative asymmetry of the two sides was introduced in several studies. [5,11] Fudickar et al reported that BIS asymmetry occurred in 12% of adults during ear-nose surgery [5] and found that asymmetry was not related to the side position during surgery. This percentage was higher than that in our study (8.9%) and might be associated with unanticipated stimulation or movement during ear-nose surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Since 'electrode one' of the BIS sensor was placed on the centre of the forehead, the left and right 'electrode one' were randomly placed above and below each other for each set of data collection. [5,7] Two BIS sensors were attached to two Aspect XP BIS monitors (Aspect Medical System, software version 3.2, Model A-2000, Natick, MA, USA). The BIS monitors were using two monitors, changing the actual monitors to avoid device bias switched sequentially to avoid any monitoring site and machine bias.…”
Section: Anaesthesia and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The dream of Robert M. Smith to have a ‘monitor of consciousness’ (49) has been at least partially fulfilled with the introduction of processed electroencephalogram. Unfortunately, these values have never been validated in children, and significant problems include differing numbers with varying agents at equal minimum alveolar concentration (MAC) (50), differences for the right and left side of the brain (51,52), higher values in children than in adults at equi‐MAC concentrations (53,54), and increases in score when sevoflurane concentrations exceed 3% (55). Although the data in adults are reasonable, the use of BIS (Aspect Medical now Covidien, Mansfield, MA, USA) and SedLine (Masimo, Inc., Irvine, CA, USA) monitors in children remains questionable, particularly for infants and neonates.…”
Section: Technology and Inventions That Improved Outcomesmentioning
confidence: 99%
“…[ 6 7 ] Differences in BIS indexes were detected in shunting patients for carotid surgery,[ 8 ] either in the presence of unilateral brain lesions[ 9 ] or during the anesthesia process. [ 10 11 ]…”
Section: Introductionmentioning
confidence: 99%